The Dynamics of Independent Power : IPPs Seed Top-to-Bottom Reform - Roseman, Elliot (World Bank, Washington, DC, 2012)
In the past few years, state power companies in many countries have offered independent power producers (IPPs) the opportunity to tender for new or existing generation. Often unrecognized is what may be an unintended consequence of introducing IPPs: they plant the seeds for a top-to-bottom change in the structure and operation of government-owned utilities. The authors review the forces at work.